Empire, Literature and “Archeology of Ignorance”: (Re-)reading Ewa Thompson’s Imperial Knowledge During the War - Riabchuk, Mykola (Porównania, 2024)
The article draws on Ewa Thompson’s concept of Imperial Knowledge as developed in her seminal book on Russian Literature and Colonialism, and understood here as a system of narratives developed by imperial ideologues (including cultural activists) with two intertwined goals: to glorify the empire, its supposedly great, “universal” culture and “unique” historical role, and, on the other hand, to undermine and depreciate the cultures of subordinate nations, deprive them of any agency and visibility. The author argues that Thompson’s book, despite some minor flaws and inaccuracies, remains highly topical, and her critical approach to imperial tenets in the most prominent works of Russian literature paves a way for much-needed deconstruction of “imperial knowledge”, that heavily influenced the West and its (mis)perceptions of Russia and Russia’s colonies.